E-Filing of Income Tax Returns - Karpagavalli, V. (Indian Journal of Computer Science, 2017)
E- Filing is a system for submitting tax documents to the Income tax department via the internet, usually without the need to submit any paper documents. Various return preparation software with e-filing capabilities is available as standalone programs or through websites or from major software vendors for commercial use. "e - File is the term for electronic filing, or sending your ITR from tax software via the Internet to the tax authority". No longer have to stand in long queues to file income tax returns. Customized return forms have been devised by the Income Tax Authority which is available on the website of the department. These forms have been devised with such details that tax payers need not file any supporting document along with. Return is submitted electronically at the site.